2001
DOI: 10.4049/jimmunol.166.3.1832
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Airway Remodeling Roles for Murine Monocyte Chemoattractant Protein-1/CCL2 During Pulmonary Exposure toAsperigillus fumigatusConidia

Abstract: Asperigillus fumigatus spores or conidia are quickly eliminated from the airways of nonsensitized individuals but persist in individuals with allergic pulmonary responsiveness to fungus. A. fumigatus-induced allergic airway disease is characterized by persistent airway hyperreactivity, inflammation, and fibrosis. The present study explored the role of CCR2 ligands in the murine airway response to A. fumigatus conidia. Nonsensitized and A. fumigatus-sensitized CBA/J mice received an intratracheal challenge of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 51 publications
3
56
0
Order By: Relevance
“…Excessive accumulation of these inflammatory cells in the lung contributes to severe immunopathology and tissue injury that precipitates tissue remodeling. 8,19,51,52,56,69 The dysregulated anti-influenza T-cell responses that we observed in infected TNF Ϫ/Ϫ or TNF-depleted hosts are likely due in part to reduced T-cell contraction following viral clearance. These results are consistent with studies of intracellular mycobacterial and LCMV infections.…”
Section: Discussionmentioning
confidence: 90%
“…Excessive accumulation of these inflammatory cells in the lung contributes to severe immunopathology and tissue injury that precipitates tissue remodeling. 8,19,51,52,56,69 The dysregulated anti-influenza T-cell responses that we observed in infected TNF Ϫ/Ϫ or TNF-depleted hosts are likely due in part to reduced T-cell contraction following viral clearance. These results are consistent with studies of intracellular mycobacterial and LCMV infections.…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, IL-10 has been found to be hepatoprotective in Con A-mediated liver damage, because Ab neutralization of IL-10 exacerbates Con A-mediated hepatic injury (10). Interestingly, several lines of evidence suggest that CCL2/MCP-1 is associated with the development of a polarized Th2 response (31,43). Therefore, in the present study, we hypothesized that the enhanced hepatic injury observed after CCL2/MCP-1 neutralization in Con A-induced hepatitis could be due to the overproduction of the Th1 cytokines TNF-␣, IL-12, and/or IFN-␥, or a decrease of the Th2 cytokine IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…with anti-MCP-1 antiserum (0.5 ml/mouse) 16 h before Con A administration as previously described (31). Control mice received heat-inactivated normal rabbit serum (NRS; Sigma-Aldrich).…”
Section: Ccl2/mcp-1 Neutralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Human IL-8/CXCL8, MCP-1/CCL2, and RANTES/CCL5 protein levels were determined in 50-l samples from cell supernatants using a standard sandwich ELISA technique previously described in detail (5). In brief, Nunc-immuno ELISA plates (Fisher Scientific, Springfield, NJ) were coated with the appropriate polyclonal capture Ab (R&D Systems), washed, and blocked with 2% BSA/PBS.…”
Section: Elisa Analysis Of Chemokine Protein In Cell Supernatantsmentioning
confidence: 99%